Role of environmental regulations, green finance, and investment in green technologies in green total factor productivity: Empirical evidence from Asian region - Tong, Lei; Chiappetta Jabbour, Charbel Jose; belgacem, Samira ben; Najam, Hina; Abbas, Jawad (Journal of cleaner production, 2022)
Promoting coordinated industrialization and environmental development is an objective set forth by the United Nations for Sustainable Development and shared by different nations worldwide. Environmental regulation (ER), green finance (GF), and increased investment in green technologies (IGT) are major initiatives in this regard. These fields have become prominent in achieving green development and climate recovery objectives. Several factors affecting green productivity growth have been analyzed in the literature; nevertheless, quantitative studies focusing on ER, GF, IGT, and green productivity are scarce. This research investigates the role of ER, GF, foreign direct investment (FDI), and IGT on GTFP in 27 Chinese provinces from 2010 to 2021. The findings reveal that strict ER significantly increases green productivity in China with a 1.826 beta value. In addition, other factors such as GF, FDI, and IGT contribute substantially to green manufacturing. This study is one of the first to integrate ER, GF, FDI, and IGT into a coherent framework of green productivity and considers the negative yield in GTFP as ignored in the previous ones. Based on empirical findings, policy implications for environmental planning in China are made. [Display omitted] •Environmental regulations (ER) significantly increase green productivity in China.•Investment in green technologies (IGT) is a significant positive predictor of green productivity in China.•Green finance (GF) initiatives contribute substantially to green manufacturing in China.•Foreign direct investment, ER, IGT, and GF help in achieving green economy objectives.